Moiré Method Based Tilt Sensing System For Landslides Monitoring Using Raspberry PI - Toh, Han Yaung (Universiti Sains Malaysia, 2019)
Landslides may lead to appalling loss such as loss of life, economic decline, decimation of infrastructure, and impacts river ecosystems. The purpose of this research is to develop a tilt sensing device based on moiré fringe pattern theory for landslide monitoring using Raspberry Pi. An algorithm to detect the centroid of the moiré fringe pattern was developed. The main advantage of using moiré fringe pattern theory is it able to show changes in pattern even it experienced tiny displacement. The prototype algorithm was tested with simulated moiré fringe pattern to prove workability of moment theory before fabricating the tilt sensing device. The effect of camera working distance onto the quality of image captured by using Logitech HD Webcam C310 was studied to determine the suitable camera working distance. The Raspberry Pi was connected with 2 different colour of light-emitting diodes (LED) to show to signal as the output. The results obtained after the centroid detection algorithm applied moiré fringe patterns produced, and it showed the algorithm manage to detect the centroid of the moiré fringe patterns and its coordinate value. Some potential improvements are suggested in this report which can be made to achieve a better and portable tilt sensing device for landslide monitoring.